Adsorption of hexavalent chromium by activated carbon obtained from a waste lignocellulosic material ( cores): Kinetic, equilibrium, and thermodynamic study - Radia Labied; Oumessaad Benturki; Adh’ Ya Eddine Hamitouche; André Donnot (Adsorption Science & Technology)
In aqueous solutions, hexavalent chromium Cr(VI) was successfully removed by activated carbon “ Z. jujuba rubidium carbonate-activated carbon” obtained from waste lignocellulosic material ( Ziziphus jujuba cores). Rubidium carbonate was used to prepare Z. jujuba rubidium carbonate-activated carbon by chemical activation using a 1:1 w/w ratio. Our results indicate that the obtained surface area of the activated carbon was equal to 608.31 m 2 /g. The adsorption study of Cr(VI) was investigated under batch conditions at constant stirring speed (220 r/min). Factors such as pH (1–6), temperature (20–40°C), adsorbent concentration (0.5–3 g/l), and initial Cr(VI) concentration (50–500 mg/l) were all studied to attain the maximum removal efficiency. Prior to the adsorption process, the morphology, elementary composition, and loss mass of activated carbon were characterized using scanning electron microscopy, X-ray fluorescence spectrometry, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Fourier transform infrared analysis of the adsorbent demonstrated the presence of key functional groups associated with the adsorption phenomenon such as those of hydroxyl and aromatic groups. The obtained results showed that the optimal conditions for a maximum adsorption efficiency are 2 for pH, 1 g/l for activated carbon dosage and 100 mg/l for Cr(VI) concentration. The removal percentage increased from 27.2 to 62.08%. The kinetic sorption was described by a pseudo-second-order kinetic equation ( R 2 ≈ 0.995). The Tóth ( R 2  = 0.997) and Elovich models were best to explain the sorption phenomenon. Thermodynamic studies showed that the adsorption of Cr(VI) onto activated carbon was feasible, spontaneous, and endothermic at 20–40°C. This novel Z. jujuba rubidium carbonate-activated carbon derived from Z. jujuba core has been found to be effective for the removal of Cr(VI) and not harmful to the ecosystem.